Economic impact on the tomato production sector of de minimis aid scheme in 2020, of sanitary crisis and pedological drought - Ancuţa Marin; Steliana Rodino; Rozi Liliana Berevoianu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The paper presents the assessment of the economic impact in the vegetable production sector through the support scheme for the Program to support tomatoes in protected areas for 2020, focusing on production results, market effects, impact on producers, trade balance. In this context, the study is based on extensive documentation on the impact of funding from the National Budget and support schemes established under European CAP regulations. The outbreak of the COVID-19 health crisis in March 2020 led to restrictions on the movement of people, which led to behavioral changes in tomato producers. The aim of this paper is to highlight the dinamics of the areas cultivated with tomatoes and, as well as to change the behavior of producers in terms of marketing and payment methods accepted.
Keywords: Q13; Q18; Q28; 330; support scheme for tomatoes; economic impact; tomato cultivation